Effect of BMI(Body Mass Index) on BMD (Bone Mineral Density) in Postmenopausal Women - Ghani, Tabassum; Paul, Subinoy Krishna; Begum, Afrina; Noorjahan, -; Sarkar, Mandira; Hussain, Taufiqua; Anar, Mosammat Gul A; Rana, Md Sohel; Hossain, Md Sazzad (Journal of Dhaka Medical College, 2020)
Menopause is commonly associated with rapid bone loss and this bone loss manifests as a significant decrease in bone mineral density (BMD). Body weight or body mass index is the most important factor which influences BMD. Aim of this study was to evaluate the association between BMI and BMD in post menopausal women. Also to measure the correlation between age, duration of menopause, weight with BMD. This cross-sectional study was undertaken in the Department of Obstetrics and Gynaecology in Dhaka Medical College Hospital, Dhaka from January, 2012 to December, 2012. The study included women of 50 to 70 years who had menopause with three or more parity. Total 100 women were evaluated by history taking, physical examination and laboratory investigation (BMD).The results showed that there was significant positive correlation between BMI and BMD value of L1-4 and total femur (Pearson‘s coefficient was +0.285, P<0.01 and +.350, P<.001). There was also significant positive correlation between weight and T- score of L1-4 (r =+ .482, P<.01) and Total femur (r = +.513, P< .01). In addition, significant negative correlation was found between BMD with age and duration of menopause. It can be concluded that in postmenopausal women as the BMI decreases bone mineral density also decreases. So, adequate weight and BMI necessary for the prevention of osteoporosis. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 60-66